Design and Development of a Web-Based Correspondence Management Information System at Politeknik Negeri Tanah Laut - Rhomadhona, Herfia; Noor Hayatie, Marliza; Pebriana, Rina (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Correspondence at Politeknik Negeri Tanah Laut (Politala) is currently still done manually in the vertical delivery process between work units. This manual process results in inefficiency, especially in monitoring the status of documents such as Staff Review Documents. Staff Review is a document that must be made by the department to the director as a basis for requesting assignment letters, decrees, recommendation letters and the others. These documents often require repeated checking, causing delays in the workflow. In addition, paper-based correspondence archives increase the risk of losing documents and make it difficult to find them again. Therefore, the implementation of the Correspondence Management Information System (SiMantan) is needed to improve the efficiency of the correspondence administration process by providing electronic document management and real-time status monitoring. This information system is built using the waterfall development model and designed with the Unified Modeling Language (UML) in the form of Usecase Diagrams. While the programming language used is the PHP programming language with the Code Ignitor 3 framework and MySQL database. Functional testing of the system is carried out using the black box testing and user acceptance testing (UAT) method which shows that all features in the information system function properly according to the expected specifications.